Walt disnep aladdin story book (Grolier Books Lahore, 2020)
Aladdin, a poor street boy, discovers a magical lamp containing a powerful genie. With the genie$1 (Bs help, he wins the heart of Princess Jasmine, battles the evil sorcerer Jafar, and saves the kingdom. The story celebrates themes of love, bravery, and the power of inner strength.s